A Preliminary Assessment of a Novel Pneumatic Unloading Knee Brace on the Gait Mechanics of Patients With Knee Osteoarthritis. Issue 10 (28th June 2013) - Della Croce, Ugo; Crapanzano, Fausto; Li, Ling; Kasi, Patrick K.; Patritti, Benjamin L.; Mancinelli, Chiara; Hunter, David J.; Stamenović, Dimitrije; Harvey, William F.; Bonato, Paolo
Abstract : Objectives: To determine whether a knee brace incorporating inflatable air bladders can alter the net peak external knee adduction moment in persons with medial compartment knee osteoarthritis. Design: Prospective cohort study. Setting: Motion analysis laboratory. Participants: Subjects (n = 18) diagnosed with knee osteoarthritis as defined by the Diagnostic and Therapeutic Criteria Committee of the American Rheumatism Association. Methods: Instrumented gait analysis was performed while subjects walked with and without the knee brace. When subjects wore the knee brace, the air bladders were either uninflated or inflated to 7 psi. The net external knee adduction moment was obtained by subtracting the abduction moment produced by the knee brace (estimated using a finite element analysis model) from the external knee adduction moment (estimated using a camera‐based motion analysis system). Main Outcome Measurements: The net external knee adduction moment was compared across all testing conditions. Results: A 7.6% decrease in net peak external knee adduction moment was observed when subjects wore the knee brace uninflated compared with when they did not wear the brace. Inflation of the bladders to 7 psi led to a 26.0% decrease in net peak external knee adduction moment. Conclusions: The results of the study suggest that the effects of an unloading knee brace may be enhanced by incorporating inflatable air bladders into the design of the brace, thus leading to an improved correction of the excessive peak external knee adduction moment observed in patients with medial compartment knee osteoarthritis.